Investigation of Seismograms of North Korean Nuclear Explosion of September 3, 2017 Recorded by the Sakarya University and Kandilli Observatory Seismic Stations - Gündüz Horasan; Levent Gülen; Hilal Yalçın; Emrah Budakoğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
A nuclear test was done on September3, 2017 in North Korea. This activity is regarded as a nuclear test based onboth CTBTO analysis and the statement of the official North Korean news agency.The type of explosion was announced as a fusion based thermonuclear hydrogenbomb. Preliminary solution of CTBTO International Data Center (IDC) reportedthe origin time, epicenter coordinates and magnitude as 03:30:01 UTC, 41.3°N129.1°E, and Mb 6.1. U.S. Geological Survey (USGS) determined these parametersas 41.343°N, 129.036 °E and body wave magnitude, Mb 6.3.In this study the seismogramsof September 3, 2017 North Korean nuclear test recorded by the SakaryaUniversity and Kandilli Observatory seismic stations will be investigated.